PENINGKATAN DETEKSI-AKSI BERBASIS DATA, INFORMASI, DAN KEJADIAN AKTUAL UNTUK PEMETAAN SITUASI KAMTIBMAS MELALUI PEMOLISIAN PREDIKTIF DALAM RANGKA PEMELIHARAAN KAMTIBMAS - Hamid, Supardi (Jurnal Ilmu Kepolisian, 2023)
This study aims to determine the increase in the base of action-detection based on data, information and actual incidents for mapping the Kamtibmas situation and to determine the maintenance of security and public order using predictive policing. This study uses a qualitative approach with a mix method that uses the level of understanding, attitude and orientation of police officers towards increased detection based on data, information and actual incidents which can be identified through surveys. These problems are then analyzed using the concept of predictive policing, the dimensions of predictive policing, and the basis for mapping the Kamtibmas situation with a predictive policing approach. The results of this study obtained that the data presented in this section are data obtained through interviews and tabulation results on the attitudes of research respondents. Respondents' attitudes towards the main issues studied in this study, which are related to increased detection of data and information-based actions as well as actual incidents which form the basis for compiling the Kamtibmas situation map. There has been an increase in requests for Harkamtibmas activity reports in the form of data and information from each function in the regional unit. Request this report in both digital and manual format. Data and information needed in addition to filling out centralized digital and manual report formats. Since the existence of the Presisi program, especially the emphasis on predictive policing, there has been an increasing push to increase action-detection activities and to expand information and data sources. As a consequence, improving personnel capabilities and improving operational activities also need adjustments. Therefore, this research needs to be socialized more periodically in order to increase the motivation, understanding and ability of personnel at the Satwil and Bag, Sat, sie levels in supporting increased action detection based on data, information and actual events and it is necessary to develop a mechanism for integrating and collaborating data and information from each part and function through a data center that can and is easily accessed.